COMPARATIVE ANALYSIS OF SELECTED PHYSICAL VARIABLES BETWEEN SCHOOL-LEVEL TENNIS AND BADMINTON PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
This research article presents a comparative investigation of selected physical variables between school-level tennis and badminton players. The study aims to explore the potential differences in physical attributes and fitness levels that may exist between young athletes participating in these two racket sports. The research contributes valuable insights into the training and development of young players in tennis and badminton, aiding coaches and educators in tailoring appropriate training programs for individual sports.